Geological and mineralogical characterization of “San José” and “La Arenosa” veins, in Santa Marianita mine of Malvas parish, Zaruma district El Oro province (Revista Científica Ciencias Naturales y Ambientales, 2019)
This study aimed to characterize the geology and mineralogy of the “San José” and “La Arenosa” veins of the Santa Marianita concession to the company Minera Blacio Aguilar located in the Zaruma canton, Province of El Oro, in southwestern Ecuador. The mineralized structures in question belong to the Zaruma-Portovelo mining district with a structural dominance of a north - south direction and a tendency to dive to the east. Mineral paragenesis was defined by macroscopic analysis of hand samples, microscopic analysis of thin sheets and polished sections that determined the mineralogical composition for the respective interpretation and comparison between both veins, for this purpose geological maps were made from topographic maps to 1: 200 scale digitized in AUTOCAD software. Sulphides, oxides and carbonates were found in polished sections along with geological indicators that defined the deposit as a low sulfidation epithermal deposit.
Keywords: Minerology; Heading; Diving; Paragenesis; Rhyolite; Epithermal deposit